COMPARATIVE STUDY OF PIG LANDRACE PERFORMANCE ON INTENSIVE MANAGEMENT AND LANDRACE PIG MAINTENANCE ON WASTE DISPOSSAL AREA, SUWUNG DENPASAR - I N. L., Sugama; Ariana, I N. T.; Oka, A. A.; Oka, A. A. (Jurnal Peternakan Tropika, 2020)
The study aimed to determine the effect of differences in maintenance with the provision of commercial feeding and waste-based feeding on Landrace pigs crossbreeding. The study used a Completely Randomized Design (CRD) with two treatments, namely the pig group with commercial feeding (BK) and the pig group with a waste-based feeding (BS). The variables observed were performance of production such as: final body weight, Avereage daily gaint (ADG), body length, height, chest gerth, hip width, and ham width. The results showed that with commercial feeding, the final body weight was 3.4% (P <0.05) higher than that of pigs which were treated with waste-based feed. This was followed by obtaining ADG and chest gerth, each of which was 7.2% and 5.0% higher in the group of pigs that were given commercial feed.For other variables found almost the same results (P> 0.05). The conclusion of this study, that with commercial feeding obtained better appearance of landrace pigs (final body weight, ADG, and chest gearth).   Keywords: Waste-based feed, appearance, landrace pig